Tourism Journalism as A Regional Tourism Promotion Media - Ratna Puspita Sari; Jokhanan Kristiyono; Edelweis Putri Prima (LPPM Stikosa - AWS, 2022)
of tourism journalism in Indonesia. They are described as having a role in promoting tourism in the area. In this research, we want to know the role of tourism journalism as a medium for regional tourism promotion using a qualitative descriptive method. Researchers conducted interviews with two travel bloggers as well as observations on their respective blogs and social media. The results of this study indicate that travel news information conveyed through blogs has developed tourism marketing communications among residents. Blog promotion media illustrates the convenience for ordinary people to participate in promoting regional tourism.